Fe-Sensitized Zeolite Supported TiO2 for the Degradation of Tetracycline Using Blue LED Irradiation - Jalloul, Ghadeer; Al-Mousawi, Assi; Chocr, Farah; Merhi, Alaa; Awala, Hussein; Boyadjian, Cassia (Frontiers in Environmental Science, 2022)
In this study, we investigated the photocatalytic degradation as a potential treatment of tetracycline (TC) antibiotic contaminated water using TiO2 semiconductor. To expand the activity of TiO2 into the visible light region and to enhance its adsorption capacity for TC, we explored its modification via sensitization with Fe ions and via immobilization on beta (BEA) zeolite support. The nano-sized beta zeolite, synthesized using the seed-assisted procedure, was used to immobilize TiO2 initially prepared by the sol-gel method. The immobilized TiO2/BEA catalyst was further ion exchanged with Fe3+ ions using FeCl3 precursor. Fe3+modified TiO2/BEA (Fe-TiO2/BEA) catalyst was characterized using SEM, XRD, BET, UV-VIS DRS, and FTIR. After the immobilization of TiO2 over BEA, the surface area of TiO2 increased from 190 to 520 m²/g and similarly its TC adsorption efficiency increased from 10% to 33%. The photocatalytic performance of the Fe-TiO2/BEA was evaluated under blue LED light for TC degradation. Fe-TiO2/BEA exhibited higher TC removal efficiency (100%) compared to TiO2 (80%) after 90 min of irradiation using 50W blue LED light for a 250 ppm initial catalyst concentration and 20 ppm TC concentration. The enhanced performance of the final catalyst was a result of the expanded surface area due to the immobilization of the TiO2 on the BEA zeolite, which resulted in an improved TC adsorption. Moreover, the presence of Fe3+ ions reduced the band gap energy of the TiO2, hence led to a red shift in its absorption spectrum to the visible light region and minimized the extent of the recombination of the charge carriers.